Rumi's influence on lower Kurdish poets (Piramird, Goran, Dilan) - محمد, د. دڵشاد على (Sulaimani Journal for Humanities, 2001)
This paper deals with a significant phenomeno with in kurdish literature; the Influence of Mawlawi on three poets of southern Kirmanji, peraMerd, Goran and Delan a phenomen on which contrasts weith the isolation of Mawlawi from his contempories Nali, Salm and Kurdi, This influence results in the emergence of the new Kurdish poetic movment of the thirties of the present certury. To uncover this fact, on the one hand, and to reach a number of new conclusions about this phenomenon and its conseguences, the research addresses three questions; When, Why and how have these three poets of kirmanji resorted to Mawlawi and his various styles? The answer to this question reveals a number of facts about the new poetic movement of the each of the three poets.